Teacher Academic Background and Learning Outcomes in BIPA Instruction: A Mixed-Methods Comparative Study - Dhani Putra Riyanto; Yupika Maryansyah (Journal of Social Work and Science Education, 2026)
This study investigates whether the learning outcomes differ between BIPA students taught by English Education graduates and those taught by Indonesian Education graduates. Employing a convergent mixed-methods comparative design, the study integrated quantitative achievement data with qualitative learner perceptions collected during the same instructional period. Quantitative data were obtained through a standardized Indonesian language achievement test assessing vocabulary, grammar, reading comprehension, and sentence construction, and were analyzed using descriptive statistics and an independent-samples t-test. Qualitative data were collected through five open-ended questions and analyzed thematically to explain and triangulate the quantitative findings. The results revealed a statistically significant difference in learning achievement between the two groups, with students taught by English Education graduates achieving significantly higher scores than those taught by Indonesian Education graduates (M = 81.83 vs. 57.00; t(58) = 8.318, p < .001). Qualitative findings reinforced these results by indicating that learners in the English Education group perceived clearer instructional explanations, greater opportunities for classroom interaction, and more supportive feedback, which helped explain their higher achievement. These findings suggest that teachers’ academic backgrounds are associated with different instructional orientations that influence BIPA learning outcomes. The study provides empirical evidence to inform BIPA teacher recruitment, professional development, and teacher education policies aimed at strengthening instructional quality in Indonesian language programs for foreign learners.